Autism : [videorecording (DVD)] : the musical - Regan, Tricia (Distributed by New Video, 2008)
Follow the extraordinary acting coach and founder of the Miracle Project musical theater program Elaine Hall, five autistic children, and their parents as they improbably, heroically mount a full-length original stage production and learn to communicate their feelings in song and performance.